Modulation of mitogenic stimuli by angiogenin correlates with in vitro phosphatidylinositol bisphosphate synthesis. - Heath, W F (1989)
125I-labeled angiogenin binds rapidly to the plasma membrane of several cell lines at 37 degrees C (t1/2 less than 1 min) but in comparatively small amounts. Competition with unlabeled angiogenin varies markedly with different cell lines, being most effective in vascular smooth muscle and fibroblast cells. Angiogenin modulates mitogenic stimuli in bovine adrenal capillary endothelial (BACE), rat aortic smooth muscle (RASM), and fibroblast (3T3) cells. Thus, it enhances the mitogenic effect of certain conditioned media on RASM and 3T3 cells, but it inhibits the mitogenic effect on BACE cells. In RASM and 3T3 cells, mitogenesis is increased at low (less than 5 ng/ml) and high (greater than 100 ng/ml) but not at intermediate concentrations of angiogenin. Plasma membranes from RASM and 3T3 cells that have been treated with angiogenin show an enhanced in vitro synthesis of phosphatidylinositol bisphosphate (PtdInsP2) with an angiogenin concentration dependence similar to that of enhanced mitogenesis. PtdInsP2 synthesis arises by activation of a fatty acid (arachidonyl) coenzyme A synthetase and either a plasma membrane fatty acid acyltransferase or phosphatidylinositol kinase(s), or both. Increased PtdInsP2 or the derived second messengers (e.g., diacylglycerol) may mediate modulation of the mitogenic stimulus. The differential mitogenic interaction of angiogenin with several cell types, either stimulation or inhibition, probably reflects the multistep nature of angiogenesis.